Maci Hass: capstone - Hass, Maci, artist (Colorado State University. Libraries, 2015)
The artist's statement: Design and illustration are two loves I've had the privilege of learning about and working in during my time at Colorado State University. I love clean design and I think simplicity is key for visual communication. An editing eye is very important and I strive to find the most basic way of communicating an idea or feeling in all of my design projects. I love bright colors and working with color within all artwork, whether that be branding, design, or illustration. My true passion is illustration. My Illustration work is inspired by personal experiences as well as pop culture. My digital work, primarily digital painting, is focused on an aesthetic I like to call 'stylized realism' that is, something that could exist based on lighting and detail, but is simplified and stylized and therefore could not really exist. I love to transport viewers past a mundane reality to somewhere else filled with endless possibilities. I consider myself a visual storyteller and I strive to create work that is recognizable and relays a story to the viewer. Perhaps the meaning isn't completely set, but by setting the tone and creating a world where a general understanding is conveyed, allows the work to act as a springboard for a viewer to create their own stories. I feel my work fits into contemporary art with attention to the modern design trends of simplicity and white space, color palettes, and use of visual storytelling techniques. I find that my commercial style of art blends well with working artists in illustration and graphic design and I am happy to keep exploring and learning as I leave Colorado State University and enter the larger art world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.